Impacts of older people's patient and public involvement in health and social care research: a systematic review. (25th June 2018) - Baldwin, Jennifer N; Napier, Sara; Neville, Stephen; Wright-St Clair, Valerie A
Abstract: Background: patient and public involvement (PPI) in research has been linked with numerous beneficial impacts, however, evidence for older people's involvement is limited. Objectives: to evaluate the impacts of involving older people in health and social care research on older co-researchers, academic researchers, and research processes and outcomes. A secondary aim was to explore critical success factors and future considerations for PPI. Design: systematic review. Methods: six databases were searched for English language articles published between 2006 and 2017. A supplementary search was conducted. Two authors independently retrieved articles using standardised inclusion criteria and data extraction forms. Articles reporting formal evaluation of older people's involvement were included. Results: nine articles, all using qualitative methodology, were included. Benefits for older co-researchers included psychological and social benefits, new learning, and activism and career opportunities, while challenging impacts comprised demanding workloads, difficult relationships and dissatisfaction with level of involvement. Benefits for academic researchers entailed new learning and shared workloads; challenges related to demanding workloads and difficult relationships. Both positive and negative effects on research quality and impact were observed. Benefits for participants and the community were demonstrated. Building relationships, facilitating communication and breaking down barriers to participation were identified as critical success factors. Conclusions: evidence for the impacts of older people's involvement is mixed although benefits appear to outweigh the challenges. Future considerations for PPI include matching older people's skills and motivations to the project and level of involvement, and establishing an iterative research process in which evaluation is embedded.